When do countries implement structural reforms? - Dias da Silva, António; Givone, Audrey; Sondermann, David (Frankfurt am Main, 2017)
"The objective of this paper is to investigate which factors macroeconomic, policy?related or institutional ? foster the implementation of structural reforms. To this objective, we look at episodes of structural reforms over three decades across 40 OECD and EU countries and link them to such factors. Our results suggest that structural reforms implementation is more likely during deep recessions and when unemployment rates are high. Moreover, the further distant from best practices, the more likely a country implements reforms. External pressures, such as being subject to a financial assistance programme, or being part of the EU Single Market facilitated pro?competitive reforms. If at all, low interest rates tend to promote rather than discourage structural reforms, while there seems no clear link between fiscal policy and reforms. Moreover, reforms in product markets tend to increase the likelihood of labour market reforms following suit. Many robustness checks have been carried out which confirm our main results."